Comparison of motivational factors for the practice of physical exercise among projects of institutionalized older adults - Moya Castro, Diego (2019)
The objective of this study is to compare the motivational factors for the practice of physical exercise in two projects for adults andelderly adults with different methodologies. The study is correlational, with an intentional sampling of 100 people (25 men and 75women), aged 50 to 73, belonging to two projects developed at the University of Costa Rica, Western Branch, which are offered twice aweek. To measure the motivational factors, the scale of the Measure of the Motives for Physical Activity-Revised (MPAM-R) was used.According to the Mann-Whitney test, the projects show significant differences in the Music, Movement and Health project (1), with respect to the Movement and Health project (2), in the dimensions: Enjoyment (Z = -2.76 / DS = 0.56), Fitness / Health (Z = -3.12 / DS = 0.28) and Competition (Z = -3.29 / DS = 0.78) (p <0.05), while in the Appearance dimensions (Z = -1.38 / DS = 1.24) and Social (Z = -1.93 / DS = 0.99) statistically significant differences were not found (p> 0.05). The differences in the reasons for the practice of physical exercise are based mainly on the methodology of project 1, the most accepted being mainly the use of music, which functions as an extrinsic motivational factor. In addition, the participants report a greater enjoyment, a better relationship between fitness, health and a positive contribution with the competition factor, in the physical exercise with dance music.